Association of smoking and smoking cessation with major causes of mortality in the Asia Pacific Region: the Asia Pacific Cohort Studies Collaboration. Issue 3 (3rd June 2008) - Barzi, F; Huxley, R; Jamrozik, K; Lam, T-H; Ueshima, H; Gu, D; Kim, H C; Woodward, M
Abstract : Background: Although the dangers of smoking, and the benefits of quitting, are well established and understood in the West, smoking remains popular among Asian men. We investigated the associations between smoking (including ex-smoking) and major causes of mortality in Asian men and women, and compared with Australians and New Zealanders (ANZ). Methods: An overview of 34 cohort studies in the Asia Pacific region involving 512 676 individuals (81 from Asia), followed up for a median of 6.7 years (20 804 deaths). Results: Mortality rates for cause-specific and all causes of mortality were systematically higher for current compared with never smokers. Hazard ratios (HR) for overall and cause-specific mortality comparing current-smokers with never smokers, ex- smokers with current-smokers and comparing numbers of cigarettes smoked per day, were higher for ANZ than Asia (p<0.001). For overall mortality, the HR (95 CI) comparing current-smoking with not was 1.37 (1.23 to 1.53) and 1.33 (1.26 to 1.40) in Asian men and women respectively. The corresponding figures in ANZ were 1.95 (1.81 to 2.09) and 1.85 (1.69 to 2.02). The HR for quitting in ANZ was 0.67 (0.63 to 0.71) and 0.66 (0.58 to 0.74) in men and women respectively. Quitting smoking had a significant benefit among Asian men, the HR was 0.88 (0.81 to 0.97) after ignoring the first 3 years of follow-up. There was no evidence of benefit for Asian women, for whom ex-smoking is rare. Conclusions: Allowing for the recent uptake of smoking in Asia, its effects are comparable to those observed in ANZ. Stringent tobacco control measures and smoking cessation strategies are urgently required in Asia.